Thermostability improvement of xylanase using error-prone polymerase chain reaction - Abdul Wahab, Mohd. Khairul Hakimi (2013)
Xylanases are widely used in commercial industries. However, not all xylanases can be used in commercial production due to their low stability and decrease in activity when reaction are performed above their optimal temperature. In this research, error-prone polymerase chain reaction (epPCR) and efficient screening strategy were used for improving thermostability of xylanase. With a 0.28% of rate mutation or 2.8 bases per 1000 bp, a library consisting of 5000 mutants was generated and was screened at 60°C for 30 minutes. The thermostability performance was improved using epPCR where four mutants were found positive. Characterization of these mutants showed different thermostability and optimal temperature among each other. Mutant DE9 showed great stability at 70°C and retained 70% of activity after 30 minutes compared to the wild type that lost 90% of its activity. At the same temperature, the other mutants such as F2B11, XC4 and X2A12 retained 57%, 52% and 62% of activity respectively. These mutants also showed significant thermostability even after pre-incubation of 60 min. Mutant DE9 retained 45% after 60 min pre-incubation, followed by XC4 (33%), F2B11 (29%) and X2A12 (29%). In contrast, the wild type xylanase totally lost its activity after 50 min pre-incubation. As for the optimum temperature, mutant DE9 and XC4 showed different optimal temperatures while the other mutants remain unchanged from the wild type xylanase. The kinetic parameter, Km for wild type xylanase was 12.86 mg/mL using beechwood xylan as substrate with Vmax 2.94 µmol/min/mL. As for the mutants; DE9 (Km: 8.91 mg/ml; Vmax: 2.04 µmol/min/mL), F2B11 (Km: 12.19 mg/mL; Vmax: 2.44 µmol/min/mL), XC4( Km: 14.21 mg/mL; Vmax: 3.11 µmol/min/mL ) and X2A12 (Km: 11.75 mg/ml; Vmax: 2.26 µmol/min/mL). Based on homology modelling, the thermostability of mutant DE9 was improved due to the substitution of non-polar amino acid which contributed in improving hydrophobicity of the enzyme although there are no changes in the formation of hydrogen bond for this mutant. On the other hand, mutant F2B11, XC4 and X2A12 showed decreased pattern in the hydrophobicity plot but there are some additional hydrogen bonds. These findings will be valuable in certain industries employing xylanases enzymatic reactions such as pulp and paper industry